(untitled) (Revista de Ciências Agroveterinárias, 2016)
This work evaluated methods of overcoming dormancy in Jatoba seeds (Hymenaea courbaril L.) by utilizing survival analysis. 75 seeds per treatment were evaluated: without treatment (T1), immersion in water at outdoor temperature for 120 h (T2) and 72 h (T3), immersion in water at 90 ºC and rest in the same water for 24 h (T4), mechanical scarification (T5) and mechanical scarification and soaking it in water for 24 h (T6). The seeds germinated per treatment were registered daily. The Kaplan-Meier method was utilized to estimate the curves of survival and median periods for the germination, the log-rank test and the Cox semiparametric model to estimate the effect of the treatments. The median periods of germination were 56 days (T4) and 33 days (T6). The seeds submitted to T4, T5 and T6 have respectively 22.5, 4.7 and 3.7 times higher capacity to germinate (shorter period for germination) than those seeds that were not submitted to overcoming dormancy.